Effect of Audit Delay, Audit Fee, Audit Tenure, and Going Concern Opinion for Voluntary Auditor Switching - Annisa Rahmadhani; Sri Rahayu; Ratih Kusumastuti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study examines the effect of audit delay, fees, tenure, and opinion going concern on voluntary auditor switching in financial sector companies listed on the IDX from 2017 to 2022. This research uses a quantitative approach with secondary data and a purposive sample of 222 companies. using logistic regression analysis with SPSS version 26. The results revealed that audit delay has a significant positive effect, while audit tenure has a significant negative effect on voluntary auditor switching. However, audit fees and going-concern opinions have no significant effect on voluntary auditor switching